The Development of Ideas on The Reform and Transformation of Islamic Family Law Into Legislation in Islamic Countries - Alex Kusmardani; Siah Khosyi’ah; Oyo Sunaryo Mukhlas; Nurrohman Nurrohman; Usep Saepullah (Syntax Corporation Indonesia, 2023)
Family Law Reform in Muslim Countries is still a debate in the Muslim World Community because it considers Islamic Family Law and Family Law to have no equality, This article aims to know the renewal and transformation of Family Law in the Islamic world. This research is a literature, with a type of analytical descriptive research, The approach used is interdisciplinary, namely comparative, juridical, philosophical, and historical approaches, while this research source uses primary sources of secondary source Law books such as theses, dissertations, and journal articles, Results of Factors Affecting the Renewal of Islamic Family Law in the World are, Politics, Economics, Social Law, Islamic Law Reform Methods are, Siyasyah al-Shar'iyyah, Takhayyur, Takhsis al-Qhadha, The old theory of Ijtihad, Ijma, Qiyas, Maslahah Mursalah, Sadd' al-Dhari'ah The Reform of Islamic Law in the World is, Polygamy, Inheritance, Marriage Registration and Marriage Agreement The transformation of Islamic Family Law in Indonesia is Law Number 1 of 1974 concerning Marriage, State Sheet Number 1 of 1974, Supplement Number 3019/1974. Presidential Instruction Number 1 of 1991 concerning the Compilation of Islamic Law which became a standard reference for judges in deciding cases. Law of 2002 concerning Child Protection, Law Number 23 of 2004 concerning Domestic Violence, Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence and these laws and regulations are in line with Islamic Family Law